The International Education Index: A global approach to education policy analysis, performance and sustainable development. (25th December 2022) - Clark, Serena; Gallagher, Ellen; Boyle, Neasa; Barrett, Michael; Hughes, Corey; O'Malley, Niamh; Ebuenyi, Ikenna; Marshall, Kevin; O'Sullivan, Katriona
Abstract: Before the COVID‐19 pandemic, the world struggled to address growing educational inequalities and fulfil the commitment to Sustainable Development Goal 4, which seeks to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. The pandemic has exacerbated these inequalities and changed how education functions, moving to online and hybrid methods. The challenges in global education highlighted and worsened by the pandemic make it necessary to re‐evaluate education systems and the policies in place to support access, quality and equal opportunity. This article focuses on analysing education policies at a national level. It tests a pilot policy analysis tool, the International Education Index (IEI), developed as a starting point to begin this reconsideration and create an accessible and comprehensive way to evaluate national education systems to inform decision‐making and policies in the new context. This research uses Ireland and Northern Ireland to test the IEI pilot tool. The IEI consists of 54 questions across nine indicators, including institutional frameworks, education strategies, digital skills and infrastructure, twenty‐first century skills, access to basic social services, adherence to international standards, legal frameworks, data gathering and availability and international partnerships. Countries can score 108 points to be categorised as having developed, emerging or nascent national education systems. Ireland scored 94 and Northern Ireland 81, indicating that they have developed national education systems.